Imigração e refúgio: as ações culturais desenvolvidas nas unidades do SESC São Paulo e sua contribuição para a construção de um currículo intercultural - Centofante, Sara Regina (2022)
This research focuses on the cultural actions of the Sociocultural Work with Refugees, developed in Sesc SP. It seeks to analyze and understand the curricular proposal of the cultural actions on the theme immigration and refuge which are taken place in the institution. Furthermore, it intends to identify how Sesc SP base its actions on the concept of non-formal education. It also investigates how the concept of reception and protagonism is developed in these actions. To this end, it is based on the comprehension of identity, cultural diversity and human rights and its contribution to the construction of a dialogical, democratic and intercultural curriculum. The theoretical framework has as main references the following authors: Maria da Glória Gohn, Paulo Freire, Michael Apple, Vera Maria Candau and Antônio Flávio Moreira. The methodology is based on Laurence Bardin’s content analysis. This study expects to present results which can contribute to welcoming and protagonism projects which are suitable for immigrants and refugees in institutions similar to Sesc SP and in schools, especially in public education